Overcoming barriers to service access: Refugees' professional support service utilization and the impact of human and social capital - Ellen Heidinger (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
After arriving in a new country, refugees are most often dependent on professional support to reestablish their livelihood. It is however well documented that refugees face barriers when seeking access to services aimed at facilitating their settlement and integration. This study examines refugees' support service needs and their actual utilization and investigates the impact of social and human capital on support service utilization. Employing data from the IAB-BAMF-SOEP Survey of Refugees, this paper highlights the diversity of refugees' support service needs as well as large differences in utilization in eight different domains. It furthermore provides evidence for an overall positive association between predictors of human and social capital and service utilization in general and additionally reveals differences in service domains. While language proficiency is positively associated with service utilization across all service domains in the sample, previous work experience in the country of origin especially increased utilization of services related to employment and the labor market. The analyses additionally find a positive association of inter-ethnic networks, whereas intra-ethnic connections are negatively associated with service utilization across a variety of domains. These findings are especially relevant since they support the hypothesis of exclusive host community knowledge, which benefits those refugees engaging with individuals outside their own ethnic network in their efforts regarding integrational outcomes. The findings of this study accentuate the need to acknowledge the diversity in refugees' service needs as well as the barriers to service utilization that only well-equipped refugees seem to be able to overcome.
Keywords: 330; refugees; service utilization; professional support services; human capital; social capital